2014
DOI: 10.1080/00221325.2014.964169
|View full text |Cite
|
Sign up to set email alerts
|

Infant Expressions in an Approach/Withdrawal Framework

Abstract: Since the introduction of empirical methods for studying facial expression, the interpretation of infant facial expressions has generated much debate. The premise of this paper is that action tendencies of approach and withdrawal constitute a core organizational feature of emotion in humans, promoting coherence of behavior, facial signaling and physiological responses. The approach/withdrawal framework can provide a taxonomy of contexts and the neurobehavioral framework for the systematic, empirical study of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
(143 reference statements)
0
9
0
Order By: Relevance
“…Therefore, the effect of the babyface schema is an important manifestation of this resource allocation strategy. However, when interacting with an infant, an adult judges the infant's physical and mental states via his or her facial expression (Sullivan, 2014). As an important emotional cue, a clearly valenced infant facial expression with a strong emotional intensity could be recognised quickly, and this recognition would be accompanied by enhanced electrocortical responses, helping the adult correctly classify the specific expression type (Peltola et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effect of the babyface schema is an important manifestation of this resource allocation strategy. However, when interacting with an infant, an adult judges the infant's physical and mental states via his or her facial expression (Sullivan, 2014). As an important emotional cue, a clearly valenced infant facial expression with a strong emotional intensity could be recognised quickly, and this recognition would be accompanied by enhanced electrocortical responses, helping the adult correctly classify the specific expression type (Peltola et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, in some studies investigating the effect of the babyface schema, neutral infant face images were mainly used as the experimental materials (Brosch et al, 2007; Cheng et al, 2015; Franklin et al, 2018; Glocker, Langleben, Ruparel, Loughead, Gur, & Sachser, 2009; Glocker, Langleben, Ruparel, Loughead, Valdez, et al, 2009; Hahn et al, 2013; Jia, Cheng, et al, 2019; Parsons et al, 2013; Parsons, Young, Kumari, et al, 2011), which greatly limited the external validity of such studies. In fact, when an adult interacts with an infant, the facial expression of the infant is an important cue for the adult to judge the infant’s physical and mental states (Sullivan, 2014). For example, a study observed that when evaluating infant faces, adults thought that happy or neutral infant faces were cuter than sad infant faces, and adults perceived a stronger self-reported willingness to adopt (Aradhye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The infant detects facial information that eventually will enable recognition and discrimination of emotion (Walker-Andrews, 1997). Furthermore, for newborn babies and infants who are highly dependent on adult care, crying and facial expressions are the main means of communicating their physiological and emotional states and needs (Sullivan, 2014). Accordingly, humans of all ages should be able to read these signals.…”
Section: Introductionmentioning
confidence: 99%
“…Approach behaviors reflect determination and autonomy-striving in response to thwarted action (C. Harmon-Jones et al, 2011; Lewis et al, 2015; Sullivan, 2014). Low levels of maternal anger in response to toddlers’ behavior may elicit greater child persistence through increased arousal or agitation.…”
Section: Discussionmentioning
confidence: 99%